2017
DOI: 10.1016/j.coviro.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection of first-trimester human placentas: utility of an explant model of replication to evaluate correlates of immune protection ex vivo

Abstract: The emergence of congenital Zika virus (ZIKV) disease, with its devastating effects on the fetus, has prompted development of vaccines and examination of how ZIKV breaches the maternal-fetal barrier. Infection of placental and decidual tissue explants has demonstrated cell types at the uterine-placental interface susceptible to infection and suggests routes for transmission across the placenta and amniochorionic membrane. ZIKV replicates in proliferating Hofbauer cells within chorionic villi in placentas from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…ZIKV is an arbovirus, with the unique ability to be transmitted vertically across the placenta. Furthermore, trimester-specific effects have been noted in humans and NHP models of ZIKV infection during pregnancy, and the timing of infection during pregnancy may influence the severity of fetal effects [2,[58][59][60][61]. We have previously shown that early gestation ZIKV infection of sheep results in fetal effects, even in the absence of detectable virus at the tissue level [25].…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV is an arbovirus, with the unique ability to be transmitted vertically across the placenta. Furthermore, trimester-specific effects have been noted in humans and NHP models of ZIKV infection during pregnancy, and the timing of infection during pregnancy may influence the severity of fetal effects [2,[58][59][60][61]. We have previously shown that early gestation ZIKV infection of sheep results in fetal effects, even in the absence of detectable virus at the tissue level [25].…”
Section: Discussionmentioning
confidence: 99%
“…30 After correcting for multiple testing, none of our analyses revealed a strong signal of a mechanism of immune control. We also saw that the dynamics of the changes in IFN concentration and levels of NK cells and CD8 effector effects observed after ZIKV infection, and shown in Figure 6, were not readily described by any of the generally used models of immune response discussed above (Equations 11,16,17) and illustrated in Figure 5C. In particular, the IFNα response showed an early peak in most, but not all, animals, but this waned in many animals before the plasma viremia was controlled, and continued to increase in some animals after plasma viral load became undetectable.…”
Section: Adaptive Immune Response Modelsmentioning
confidence: 99%
“…Not only is ZIKV detected in blood, it widely disseminates, with viral particles being detected in easily sampled compartments, such as urine, semen, and breast milk . Understanding the rapid viral kinetics and widespread dissemination of ZIKV, including its apparent ability to cross both the blood‐brain barrier and the placental barrier will be vital in assessing and reducing infection risks, and to evaluate the effectiveness of therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitation of the virus suggests that both amniotic and villous cytotrophoblast cell populations are more susceptible to infection earlier in gestation . Hofbauer cells are a target of Zika virus once inside the villous stroma . Virions are detected in the amniotic fluid, yet it is unclear which population described above is the main reservoir of the virus.…”
Section: Part II the Histopathology Of Placental Infectionmentioning
confidence: 99%